Desmin interacts with STIM1 and coordinates Ca2+ signaling in skeletal muscle - Hengtao Zhang; Victoria Graham Bryson; Chaojian Wang; TianYu Li; Jaclyn P. Kerr; Rebecca Wilson; Deborah M. Muoio; Robert J. Bloch; Christopher Ward; Paul B. Rosenberg (JCI Insight, 2021)
Stromal interaction molecule 1 (STIM1), the sarcoplasmic reticulum (SR) transmembrane protein, activates store-operated Ca2+ entry (SOCE) in skeletal muscle and, thereby, coordinates Ca2+ homeostasis, Ca2+-dependent gene expression, and contractility. STIM1 occupies space in the junctional SR membrane of the triads and the longitudinal SR at the Z-line. How STIM1 is organized and is retained in these specific subdomains of the SR is unclear. Here, we identified desmin, the major type III intermediate filament protein in muscle, as a binding partner for STIM1 based on a yeast 2-hybrid screen. Validation of the desmin-STIM1 interaction by immunoprecipitation and immunolocalization confirmed that the CC1-SOAR domains of STIM1 interact with desmin to enhance STIM1 oligomerization yet limit SOCE. Based on our studies of desmin-KO mice, we developed a model wherein desmin connected STIM1 at the Z-line in order to regulate the efficiency of Ca2+ refilling of the SR. Taken together, these studies showed that desmin-STIM1 assembles a cytoskeletal-SR connection that is important for Ca2+ signaling in skeletal muscle.